2014
DOI: 10.1111/1462-2920.12519
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial community shift is induced by dynamic environmental parameters in a changing coastal ecosystem (northern Adriatic, northeastern Mediterranean Sea) – a 2‐year time‐series study

Abstract: The potential link between the microbial dynamics and the environmental parameters was investigated in a semi-enclosed and highly dynamic coastal system (Gulf of Trieste, northern Adriatic Sea, NE Mediterranean Sea). Our comprehensive 2-year time-series study showed that despite the shallowness of this area, there was a significant difference between the surface and the bottom bacterial community structure. The bottom bacterial community was more diverse than the surface one and influenced by sediment re-suspe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
51
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(59 citation statements)
references
References 78 publications
(117 reference statements)
7
51
0
Order By: Relevance
“…In contrast, the high proportion of chloroplast-affiliated clones obtained from marine snow in December indicates a phytoplankton origin of the marine-snow matrix (Fig. 4), most likely derived from the diatom bloom that typically occurs in late autumn (Mozeti et al 2012) and which was also observed in December 2009 (Tinta et al 2014). However, the presence or high abundance of bacterial groups characteristic of low salinity estuarine or fresh waters, like Betaproteobacteria, Verucomicrobia and Actinobacteria (Kirch man et al 2005, Alonso et al 2010) might indicate a freshwater origin for a part of the bacterial community detected in marine snow in December.…”
Section: Prokaryotic Community Structure Is Influenced By Season or Lmentioning
confidence: 94%
“…In contrast, the high proportion of chloroplast-affiliated clones obtained from marine snow in December indicates a phytoplankton origin of the marine-snow matrix (Fig. 4), most likely derived from the diatom bloom that typically occurs in late autumn (Mozeti et al 2012) and which was also observed in December 2009 (Tinta et al 2014). However, the presence or high abundance of bacterial groups characteristic of low salinity estuarine or fresh waters, like Betaproteobacteria, Verucomicrobia and Actinobacteria (Kirch man et al 2005, Alonso et al 2010) might indicate a freshwater origin for a part of the bacterial community detected in marine snow in December.…”
Section: Prokaryotic Community Structure Is Influenced By Season or Lmentioning
confidence: 94%
“…Alteromonas produces and secretes a variety of extracellular enzymes that contribute to the hydrolysis of biopolymers, including polysaccharides (253)(254)(255)(256)(257), proteins (258,259), nucleic acids (260,261), and lipids (262), the major components of marine POM. Alteromonas and related species respond rapidly to phytoplankton blooms and especially to elevated POC concentrations (109,(263)(264)(265). Algal exudates from a variety of phytoplankton can be utilized by Alteromonas, making them a major microbial group in algal phycospheres (266)(267)(268).…”
Section: Impacts Of Surface-associated Microbiota On Ocean Carbon Seqmentioning
confidence: 99%
“…creasing incidence of human vibrio illnesses worldwide are linked to phytoplankton blooms, ocean warming, and the capacity of vibrios to colonize surfaces (15,265,(560)(561)(562)(563)(564). Higher temperature also significantly increases population abundance and upregulates virulence determinants such as motility, resistance to antimicrobial compounds, hemolysis, and cytotoxicity in coral pathogens (565,566).…”
Section: An Example Of Microbial Interaction With Surfaces: Vibrio Chmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies describing Adriatic picoplankton diversity mainly focused on coastal waters (11,12). In addition, temporal studies were exclusively done in the northern coastal waters (13)(14)(15)(16). Deep winter convective mixing was shown to shape the community structure via the transport of nutrients, i.e., phosphorus and nitrogen, to the euphotic zone, consequently triggering blooms of photosynthetic microorganisms in early spring (17).…”
mentioning
confidence: 99%